Exogenous DA-6 Improves the Low Night Temperature Tolerance of Tomato Through Regulating Cytokinin - Lu, Jiazhi; Guan, Pengxiao; Gu, Jiamao; Yang, Xiaolong; Wang, Feng; Qi, Mingfang; Li, Tianlai; Liu, Yufeng (Frontiers in Plant Science, 2021)
Low night temperature (LNT) causes environmental stress and has a severe and negative impact in plant growth and productivity. Synthetic elicitors can regulate plant growth and induce defense mechanisms from this type of stress. Here, we evaluated the effect of the exogenous growth regulator diethyl aminoethyl hexanoate (DA-6) in tomato leaves response to LNT stress. Our results showed that exogenous DA-6 activates the expression of chlorophyll synthesis and photosystem-related genes, and results in higher photosynthetic activity and chlorophyll production. Furthermore, DA-6 can regulate the synthesis of endogenous cytokinin (CTK) and the expression of decomposition genes to stabilize chloroplast structure, reduce oxidative damage and maintain the photochemical activity of tomato leaves under LNT stress. DA-6 maintains a high level of ABA content and induces the expression of CBF genes, indicating that DA-6 may participate in the cold response signaling pathway and induce the expression of downstream low temperature response genes and accumulation of compatible osmolytes. This study unravels a mode of action by which plant growth regulators can improve low temperature tolerance and provides important considerations for their application to alleviate the harmful effects of cold stress.